Removal of boron from waste waters using HDTMA-modified zeolites - Demirçivi, Pclin; Nasün-Saygili, Gülhayat (Elsevier BV, 2010)
In this study, boron removal is implemented by adsorption process using modified natural zeolite. Due to natural zeolites have no affinity for anions, Hexadecyltrimethylamine (HDTMA) was used to modifiy natural zeolites. Experiments were run in both batch and column systems. Batch studies were performed to investigate the effects of various experimental parameters, such as optimum HDTMA loading level, adsorbent dose, initial concentration and pH, on the removal of boron. It is found that removal of boron increases while adsorbent dose and initial concentration increase at the optimum pH level 8.5 and HDTMA loading level 100%. Equilibrium isotherms of batch system were also analyzed by Langmuir and Freundlich isotherm models. Freundlich isoterm model represents the sorption process very well for batch system. Effect of bed height, flow rate and initial concentration on boron removal were investigated in column experiments. All the solutions that were used for the column system were adjusted optimum pH leve...